Accuracy of multiparametric MR imaging with PI-RADS V2 assessment in detecting infiltration of the neurovascular bundles prior to prostatectomy. Issue 98 (January 2018) - Sauer, Markus; Weinrich, Julius M; Fraune, Christoph; Salomon, Georg; Tennstedt, Pierre; Adam, Gerhard; Beyersdorff, Dirk
Highlights: Targeted assessment of infiltration of the neurovascular bundles using mpMRI has high specificity and moderate sensitivity. If preoperative mpMRI determines NVB infiltration, patient and surgeon must consider extended non-nerve-sparing surgery. PI-RADS V2 demonstrates limited eligibility to evaluate NVB infiltration. Future revisions should be revised accordingly. Abstract: Objectives: To evaluate the accuracy of assessment of neurovascular bundle (NVB) infiltration using multiparametric magnetic resonance imaging (mpMRI) and PI-RADS V2 prior to prostatectomy. Methods: The ethics committee approved this retrospective study with waiver of informed consent. N = 198 consecutive patients with biopsy proved cancer underwent standardized mpMRI at 3T prior to surgery. NVB infiltration was assessed for each side (a total of 396). Maximum PI-RADS V2 scores were determined for the posterolateral areas adjacent to the NVBs. Imaging results were correlated with postoperative pathology and standard descriptive statistics were calculated. Results: Overall T-staging sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy of mpMRI were 64.4%, 89.2%, 82.4%, 76.2% and 78.3%, respectively. In 396 cases NVB infiltration was predicted with 75.3%, 94.0%, 80.2%, 92.1 % and 89.4 % sensitivity, specificity, PPV, NPV and accuracy, respectively. Analyses of 396 NVB and their adjacent PI-RADS V2 scores with pathology revealed significantly more NVB-infiltrations in suspect scores of 5 and 4 vs. uncertain scores of 3–1 (81/264 vs. 16/132, p = 0.0001). Considering scores higher than 3 as a criterion of infiltration demonstrated moderate sensitivity and poor specificity (83.5% and 38.8%, respectively). Interobserver agreement of a second reading of a random sample was good (κ = 0.64) for NVB infiltrations and moderate (κ = 0.59) for PI-RADS V2. Conclusions: Assessment of infiltration of the neurovascular bundles using mpMRI has valuable diagnostic performance, yet PI-RADS V2 Scores demonstrate limited eligibility. Combined findings offer crucial information for the planning of prostatectomy.